EFFORTS TO INCREASE MATHEMATICS LEARNING OUTCOMES ON NUMBER AND INFINITE SEQUENCES THROUGH THE METHOD OF GIVING PRE-LEARNING ASSIGNMENTS TO CLASS XI IPA-4 SMA NEGERI 12 BANDA ACEH - Maryati Maryati (Prodi Tadris Matematika Universitas Muhammadiyah Aceh, 2021)
Attention and seriousness in the implementation of learning so that the process and learning outcomes increase. Teachers have not at all considered appropriate ways and methods to improve learning outcomes. To overcome the learning outcomes achieved, the authors will conduct this research so that learning outcomes increase by using the Pre-learning assignment assignment method. The purpose of this research is to improve the mathematics learning outcomes of class XI students. This type of research is classroom action research. This research was carried out for 3 months, namely in January-March of the 2018/2019 school year. The research subjects were students of class XI IPA-4 for the 2018/2019 academic year. The number of students as many as 30 people, consisting of 11 female students and 19 male students. Data collection was carried out using test techniques, observation and student learning outcomes. The data analysis technique used the equation X = ?N/n. The results of the study showed that through the provision of pre-learning assignments could improve the mathematics learning outcomes of class XI IPA-4 students of SMA Negeri 12 Banda Aceh. Student learning outcomes in learning Infinite Rows and Series have increased after students experienced learning by giving pre-learning assignments. This is evident from the comparison of the average value obtained by students in the implementation of learning cycle I to cycle II. In the evaluation tests of 3 meetings I and II the averages obtained were 63.23 and 65.3, while in the evaluation tests of 2 meetings I and II the averages obtained were 65.33 and 68.4.